- Absorption:
A) x + xy = x
B) x (x+y) = x
AXIOMS AND BASIC THEOREMS
Absorption x+x·y =x x · (x + y) = x
A Boolean function that is expressed in algebraic form can be simpli-
fied using the axioms and theorems of Boolean algebra
⊳ Example 1: OR form of the Absorption Theorem
x + x · y = x · 1 + x · y = x · (1 + y) = x · 1 = x
⊳ Example 2:
x+x·y =x+x·y+x·y
=x·x+x·y+x·x+x·y
= (x + x) · (x + y) = 1 · (x + y)
=x+y
⊳ Example 3:
x · (x + y) = x · x + x · y = x + x · y = x
https://docs.google.com/viewer?a=v&q=cache:vvf4G4lWnnAJ:www.utdallas.edu/~cantrell/ee2310/boole.pdf+&hl=en&pid=bl&srcid=ADGEESj4MkhQetdjm9j72t0ctUL72kuNtjfsvEj1V1PBxgT-7MA4H8LUy8dbKmiyKynFtuvNt55_e2cse30bftRNM54OKhpZQIhpSeaCnAdFDOCR5gK5ryrCifFWMzSZAdx0eTf3B3UT&sig=AHIEtbTv69hjBdYNTZXQUWraukrH9OMagg
- (Absorption 1) x∧(x∨y) = x
(Absorption 2) x∨(x∧y) = x
http://en.wikipedia.org/wiki/Boolean_algebra
- Redundancy laws
The following laws will be proved with the basic laws. Counter-intuitively, it is sometimes necessary to complicate the formula before simplifying it.
Absorption
x + x · y = x
Proof:
x + x · y
= x · 1 + x · y
= x · (1 + y)
= x · 1
= x
x · (x + y) = x
Proof:
x · (x + y)
= (x + 0) · (x + y)
= x + (0 · y)
= x + 0
= x
http://nayuki.eigenstate.org/page/boolean-algebra-laws
No comments:
Post a Comment